Micropolitiques. - Ardenne, Paul; Buren, Daniel; Macel, Christine; Restany, Pierre (Grenoble : Magasin - Centre National d'Art Contemporain, 2000)
Atelier van Lieshout ; Beuys, Joseph ; Blocher, Sylvie ; Boucherot, Marc ; Buren, Daniel ; Cadere, Andre ; Durham, Jimmie ; Filliou, Robert ; Geers, Kendell ; Gonzalez-Torres, Felix ; Green, Gregory ; Höller, Carsten ; Hubaut, Joel ; Kolle, Regine ; Lucariello, Saverio ; Manlik, Florence ; Matta-Clark, Gordon ; Medalla, David ; Nankervis, Adam ; Meste, Philippe ; Name Diffusion ; Paraponaris, Hervé ; Peterman, Dan ; Pistoletto, Michelangelo ; Rehberger, Tobias ; Scurti, Franck ; Starling, Simon ; Tzaig, Uri ; Uriburu, Nicolas ; Villeglé, Jacques
biog. + bibliog. p. 62-78 (The bibliographies focus on writings by the artists themselves).
Frans & Engels
Micropolitiques, Magasin - Centre National d'Art Contemporain de Grenoble, 06.02. - 30.04.2000
boek